Effect of Stress, Organizational Culture, Motivation on Organizational Citizenship Behaviour at Pati Police Resort - Herdiany, Hapsari Dyah (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2019)
This study aims to determine the Influence of the Effect of Job Stress, Organizational Culture Work Motivation Against Organizational Citizenship Behavior At Pati Police Resort. The sample in this research is Resort Police Officer Pati which amounted to 149 respondents. Sampling technique in this research is with non probability sampling. Methods of data analysis used dalah Test validity, reliebilitas and multiple linear regression analysis test with t test, F test, and coefficient of determination (R2). From the hypothesis test showed that work stress and work motivation have an effect on Organizational Citizenship Behavior, for Organizational culture has no effect on Organizational Citizenship Behavior.